Brain mapping - Blaž Koritnik (Psihološka Obzorja, 2004)
Cartography of the brain ("brain mapping") aims to represent the complexities of the working brain in an understandable and usable way. There are four crucial steps in brain mapping: (1) acquiring data about brain structure and function, (2) transformation of data into a common reference, (3) visualization and interpretation of results, and (4) databasing and archiving. Electrophysiological and functional imaging methods provide information about function of the human brain. A prerequisite for multisubject, multidimensional and multimodal mapping is transformation of individual images to match a standard brain template. To produce brain maps, color, contours, and other visual cues are used to differentiate metabolic rates, electrical field potentials, receptor densities, and other attributes of structure or function. Databases are used to organize and archive data records. By relating the maps to cognitive functions and psychological models, brain mapping offers a prerequisite for the understanding of organizational principles of the human brain.